DAMPAK FINANCIAL TECHNOLOGY DAN STRATEGI MANAJEMEN OPERASI PADA CV SINAR SETUJU KOTA PALOPO - Bustami, Taufik; Budiandriani, Budiandriani; Suriyanti, Suriyanti (Universitas Muhammadiyah Tangerang, 2024)
Operations management is a series of activities that convert input into output, both goods and services, through a process of planning, organizing, directing and supervising activities. Operations managers are responsible for managing the parts of a business or organization that produce goods or services. The research results showed that the impact of financial technology and CV Sinar Sejuju's operational management strategy is to maintain the quality of goods and provide the best service for consumers as well as providing digital payments or Qris or similar. The design of the product to be produced is seen from its ease of management and ability to attract consumers and must be in accordance with the owner's decision. Strategic location. Layout that can make work easier. Human resources who have qualified skills. Carrying out promotional activities to be known by many groups. Implementation of liquidity management to avoid shortages of goods. The maintenance carried out has been carried out optimally starting from the warehouse, production equipment and raw materials.